A model-based economic evaluation of four newborn screening strategies for cystic fibrosis in Flanders, Belgium. Issue 3 (3rd May 2020) - Schmidt, Masja; Werbrouck, Amber; Verhaeghe, Nick; De Wachter, Elke; Simoens, Steven; Annemans, Lieven; Putman, Koen
ABSTRACT: Objectives : The most cost-effective newborn screening strategy for cystic fibrosis (CF) for Flanders, Belgium, is unknown. The aim of this study was to assess the cost-effectiveness of four existing newborn screening strategies for CF: IRT-DNA (immunoreactive trypsinogen, cystic fibrosis transmembrane conductance regulator ( CFTR ) gene mutation analysis), IRT-PAP (pancreatitis-associated protein), IRT-PAP-DNA, and IRT-PAP-DNA-EGA (extended CFTR gene analysis). Methods : Using data from published literature, the cost-effectiveness of the screening strategies was calculated for a hypothetical cohort of 65, 606 newborns in Flanders, Belgium. A healthcare payer perspective was used, and the direct medical costs associated with screening were taken into account. The robustness of the model outcomes was assessed in sensitivity analyses. Results : The IRT-PAP strategy was the most cost-effective strategy in terms of costs per CF case detected (€9314 per CF case detected). The IRT-DNA strategy was more costly (€13, 966 per CF case detected), but with an expected sensitivity of 93.4% also the most effective strategy, and was expected to detect 2.2 more cases of CF than the IRT-PAP strategy. The incremental cost-effectiveness ratio of IRT-DNA vs. IRT-PAP was €54, 180/extra CF case detected. The IRT-PAP-DNA strategy and the IRT-PAP-DNA-EGA strategy were both strongly dominated by the IRT-PAP strategy. Conclusion : The IRT-PAP strategy was the most cost-effective strategy in terms of costs per CF case detected. However, the strategy did not fulfil the European Cystic Fibrosis Society guidelines for sensitivity and positive predictive value. Therefore, the more costly and more effective IRT-DNA strategy may be the most appropriate newborn screening strategy for Flanders.